2018
DOI: 10.4081/ija.2018.937
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of wild perennial grasses as a biomass source in semi-arid Mediterranean environments

Abstract: In Mediterranean environments, few perennial grass species are available for cultivation in rainfed systems and marginal lands, where plants with excellent adaptation are required. The aim of the present work was to determine the potentiality of five native Mediterranean perennial grasses for lignocellulosic biomass production. Wild accessions of three hemicryptophytes (Ampelodesmos mauritanicus, Hyparrhenia hirta, and Piptatherum miliaceum) and two geophytes (Saccharum spontaneum ssp. aegyptiacum and Sorghum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…A similar downward trend was previously observed in the study by Cosentino et al [22], where rainfed Saccharum crops showed higher hemicellulose, cellulose, and lignin than mid and full irrigated crops. Biomass composition in Saccharum was comparable with levels found for many other perennial grasses, such as Miscanthus × giganteus, Miscanthus sinensis, Arundo donax, Cymbopogon hyrthus, Sorghum halepense, Oryzopsis milianea, and Panicum virgatum [21,25,26,56,57].…”
Section: Discussionsupporting
confidence: 63%
“…A similar downward trend was previously observed in the study by Cosentino et al [22], where rainfed Saccharum crops showed higher hemicellulose, cellulose, and lignin than mid and full irrigated crops. Biomass composition in Saccharum was comparable with levels found for many other perennial grasses, such as Miscanthus × giganteus, Miscanthus sinensis, Arundo donax, Cymbopogon hyrthus, Sorghum halepense, Oryzopsis milianea, and Panicum virgatum [21,25,26,56,57].…”
Section: Discussionsupporting
confidence: 63%
“…In the current study, however, the large sample sizes obtained per taxon, the replication of each taxon within and among 2–4 populations, and the statistical control of variation in other plant attributes that are correlated with instantaneous gas exchange rates (e.g., leaf position on the stem, leaf temperature at the time of measurement, and the life cycle stage at which plants are measured) helped to account for the variance in physiological performance that can obscure differences between taxa. Numerous other recent studies have compared taxa, experimental treatments, or life history stages based on instantaneous gas exchange measurements (Mazer et al, 2010; Franks, 2011; Dudley et al, 2012, 2015; Gorai et al, 2015; Cheng et al, 2017; Gulias et al, 2018; Velikova et al, 2018; Wang et al, 2019; Scalon et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The most recent Intergovernmental Panel on Climate Change report [20] forecasts that climate change will expose plants to increasing occurrences of combined abiotic stresses, including drought, higher temperatures, and increased atmospheric CO 2 concentrations in the coming decades. This would be especially intense in the Mediterranean basin, which is characterized by 2-6 months of drought periods in summer and shorter drought winter periods from autumn to spring [21]. Thus, the crops grown in the semi-arid Mediterranean area could be subjected to multiple stresses that are directly related to climate change.…”
Section: Introductionmentioning
confidence: 99%